answer to this question plse ????

*sort by* **best** latest

Would this be x^6+ax^5+x^4-x^3+3x-a2

Assuming this is a binomial expansion ie all terms are a, then

(-a)^6=-2a or a=-(2)^1/5.

However, if this is a binomial expansion. then this says 6a^5=3 and that is not true if a =-(2)^1/5

So lets iterate and let a=1, then assume it is 1 of six possible roots.

Then we have (-1)^6 -a(-1)^5+(-1)^4-(-1)^3+3(-1) -2a=1+a+1+1-3-2a=0

or

-a=0 or -1=0 which means that -1 is not a root and a is therefore not 1.

Lets test a=-1............so we have (1)^6-a(1)^5+(1)^4-(1)^3+3(1)-2a=

1-a+1-1+3-2a=0 and 4+3 does not equal 0

Lets try a=2

We then have(-2)^6-a(-2)^5+(-2)^4-(-2)^3+3(-2)-2a=64+32a+16-8-6-2a which doesn't equal 0..

Without going into specifics, letting a equal any integer larger than 2 will not cause a 0.

I don't believe there is an integer solution for this. I used to have a calculator that would solve this. This is an iterative problem and is solved by converging on the answer.

I don't have the time but would guess a is between 0 and 1. Just an educated guess. :D

Maybe I don't understand what equation you are using.

This cant be a binomial expansion and it converges above 2 and less than -2. This needs to be iterated until you converge on an answer. Unless someone has a graphing calculator :D.

You can help the HubPages community highlight top quality content by ranking this answer up or down.

Did you miss some operators? Otherwise, are there supposed to be some parentheses around the exponents. I'm not sure what the expression is supposed to be.

You can help the HubPages community highlight top quality content by ranking this answer up or down.

You might find it in the textbook you were probably supposed to study.

You can help the HubPages community highlight top quality content by ranking this answer up or down.